Prenatal Valproic Acid Exposure Affects Song Learning in Zebra Finches: A Potential Model for Vocal Development in Autism - Estifanos Ghebrihiwet Tewelde; Boglárka Morvai; Gergely Zachar; Ákos Pogány (Life)
Autism spectrum disorder (ASD) encompasses a range of neurodevelopmental conditions characterized by impairments in social abilities and communication. Studying appropriate animal models can enhance our understanding of the neural mechanisms underlying these conditions, potentially leading to improved treatment and intervention strategies. Modeling impairments in linguistic development and vocal communication caused by autism had been a challenging goal for a long time. Prenatal valproic acid (VPA) treatment has been successfully used to induce ASD-like behavioral symptoms in several vertebrate species including birds. Applying VPA-treatment on songbirds, therefore, offers a promising research paradigm to model ASD. In this study, we investigated the effect of embryonic VPA treatment on song learning in the highly social zebra finch (Taeniopygia guttata). Fertilized eggs were injected with either 0.45 µmol VPA or a saline solution on day 9 of incubation, and hatchlings were allowed to stay with their parents until day 35 post-hatching to facilitate song learning from the father. Once male offsprings reached adulthood, their songs were recorded and compared to those of their fathers. VPA-exposed males exhibited significantly greater similarity to their fathers’ songs compared to control males (74% vs. 31%, respectively), suggesting a reduced ability to modify and develop their own vocal patterns as subadults. Additionally, they showed higher entropy in their songs compared to controls (−1.4 vs. −1.7), indicating more disorganized vocalizations. These findings suggest that prenatal VPA exposure disrupts typical song learning and vocal development in zebra finches, likely by affecting neural mechanisms involved in vocal learning and crystallization of the songs. Our study suggests VPA treatment in songbirds provides a useful tool to model and investigate linguistic developmental disorders related to ASD in humans.